Analisis Komparasi Kepercayaan Merek (Brand Trust), Store Atmosphere, Kualitas Layanan dan Repurchase Intention Pada Clarice Beauty Clinic Dan Loris Beauty Clinic Di Kota Surabaya - Nisa, Suci Rohmatun; Maruta, M.M, Dr. IGN Anom (Research Journal of Social Science and Economics, 2025)
This research was conducted with the aim of knowing whether there are differences between Brand Trust, Store Atmosphere, Service Quality and Repurchase Intention at Clarice Beauty Clinic and Loris Beauty Clinic. Thv lis ty lpe o lf resea lrch u ses quantitative research methods and researchers try to make comparisons between the variables attached to the two objects, namely Clarice Beauty Clinic and Loris Beauty Clinic. Comparative research is research that is comparative. This research was conducted by distributing questionnaires via Google from t lo consumers who had facial treatments or purchased products at Clarice Beauty Clinic and Loris Beauty Clinic. Th le sam lpling tech lnique u lsed in th lis stu ldy is non-probability samp lling (non-rando m sampling) because this research is specifically for consumers who have had facial treatments or purchased products at Clarice Beauty Clinic and Loris Beauty Clinic using the snowball sampling technique. Using the data analysis method, the homogeneity test functions to find out whether the variation is uniform in each sample and the independent sample t-test to find out whether there is a difference in the mean or average of two sample groups that are not related and assisted with SPSS 20. From Th le re sults of data an alysis techniques obtained show that Brand Trust, Store Atmos lphere, Service Quality and Repurchase Intention do not have differences in Clarice Beauty Clinic and Loris Beauty Clinic. Keywords: Brand Trust, Store Atmosphere, Service Quality, Repurchase Intention